Relationship Between Child Marriage with Reproductive Health and Cervical Neoplasia in Karnali, Nepal - Niresh Thapa; Muna Maharjan; Girishma Shrestha; Narayani Maharjan (Journal of Karnali Academy of Health Sciences, 2021)
Background: Child marriage (marital age less than 18 years) is recognized as a violation of human rights. However, it remains a deep-rooted social problem in Nepal. We aimed to find out the relationship between child marriage and reproductive health and cervical neoplasia.